Hubungan Tingkat Kemampuan Bahasa Inggris dengan Kualitas Pengalaman Magang - Ceria Amila Akyas; Wahyu Budi Priatna; Leonard Dharmawan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
English has become an essential competence in higher education, particularly in preparing students to face the demands of a globalized and digitally driven labor market. In the field of digital communication and media, English is not only used as a medium of communication but also as a key tool for accessing global information, digital platforms, and professional standards. Internship programs serve as experiential learning processes that bridge academic knowledge and real-world professional practice, where language proficiency plays a crucial supporting role. This study aims to examine the relationship between English language proficiency and the quality of internship experiences among students of the Digital Communication and Media Study Program. The research is grounded in employability skills and experiential learning concepts, emphasizing the importance of communication competence in workplace readiness. A quantitative descriptive-correlational method was employed, with data collected through a Likert-scale questionnaire measuring students’ English proficiency across listening, speaking, reading, and writing skills, as well as internship experience quality in terms of task relevance, skill development, adaptability, confidence, and professional networking. The findings indicate that students generally demonstrate adequate English proficiency and positive internship experiences. Furthermore, the results reveal a positive and significant relationship between English proficiency and the quality of internship experience. These findings suggest that students with stronger English skills tend to engage more effectively in internship activities and gain higher-quality learning outcomes. In conclusion, English proficiency plays a significant role in enhancing students’ internship experiences and supports their professional readiness in the digital communication and media industry.